Checklist of the Free-Living Marine Nematodes of the Iberian Peninsula (north east Atlantic) - Besteiro, Celia; Ayora, Mario (Zootaxa, 2017)
A Checklist of the Free-Living Marine Nematodes of the Iberian Peninsula, based on the literature published to date, is presented in this paper. The localities where the taxa were collected, as well as the habitats and depths where they were found, are also mentioned. All references to date provide a total of 236 species, 142 genera and 37 unidentified families. Also, the preparation of the present Checklist allowed us to clarify some errors that have been dragging on for some time and make a few clarifications, all of them based on a review of the original papers.